EDUCATIONAL TECHNOLOGIES OF SITUATIONAL MODELING FOR THE FORMATION OF JUNIOR SCHOOLCHILDREN’S ENVIRONMENTAL AWARENESS: EXPERIENCE DURING THE WAR - Vlasenko, Nataliia (Studies in Comparative Education, 2022)
The key technologies of situational modeling for the formation of junior schoolchildren’s environmental awareness are considered in the article. It is determined that it is advisable to use educational technologies of situational modeling for junior schoolchildren’s environmental awareness formation, namely simulations or simulation games, simplified court hearings (court prose), public hearings, role-playing (role play, skit play, dramatization). To apply situational modeling technologies, the teacher should create a problematic situation of environmental content, and children - during the discussion - should suggest a possible solution that will contribute to their environmental awareness. It is established that educational technologies of situational modeling develop children’s critical thinking, ability to express their thoughts, and find an approach to solving particular environmental and situational problems. They also offer ways of rational use, protection, and preservation of the environment that are effective in primary school for pupils’ awareness. Educational technologies of situational modeling, i.e., the Green City of the Future simulation game, were practically used to develop environmental awareness of junior schoolchildren and their parents, who were internally displaced persons during the war. It is determined that interactive technologies complement the traditional approach to learning because students become active participants in the educational process in modern realities. They are at the center of the interaction of its participants, have the opportunity to show their knowledge and determine their level, and learn to work in a team. While forming environmental competence and responsibility, primary school teachers and pupils design a new system of values that includes knowledge of nature, patterns of behavior that improve the environmental situation and interaction with the environment, conserve environmental resources and increase their environmental awareness. Play activities are designed to figuratively and easily explain to the child the essence of environmental issues and the reasons for their occurrence to help meaningfully perceive the world around us and the changes taking place in it, especially during martial law. Simulation games are easily integrated into the usual course of classes or leisure activities, making them more diverse and productive for all participants in the educational process.